An Organizational Diagnosis for Change Readiness: A Case of the Department of Special Education - Sahib Khan, Muhammad Uzair Ul Hassan, Iram Parveen, (JIE, 2024)
This study aims to conduct an organizational diagnostic (OD) within the Department of Special Education in order to evaluate its readiness for change. Data was collected from a sample of 1,200 individuals, including heads of the top, middle, and bottom tiers within the department. The Organizational Diagnostic Questionnaire (ODQ), based on Weisbord's six-box model, was used to gather information. A total of 506 respondents willingly completed the ODQ survey. The findings revealed that the department staff has a strong understanding of the organizational objectives. However, there are several areas that hinder optimal performance, such as limited employee engagement in departmental discussions, centralized decision-making, irrational work distribution, and inadequate resource allocation. In addition, poor communication, inefficient help-seeking methods, unsatisfactory promotions, restricted knowledge sharing, strained inter-relationships, conflicts, and ineffective help-seeking processes all impede effectiveness.